Membangun Keterampilan Berargumentasi Siswa Melalui Metode Diskusi Pada Mata Pelajaran Aqidah Akhlak di MA Muhammadiyah 01 Jember - Anggun Ning Tyas; Sofyan Rofi; Dhian Wahana Putra (Jurnal Ilmu Pendidikan, Sosial dan Humaniora, 2025)
This study aims to describe the implementation of the discussion method in developing students' argumentation skills in Aqidah Akhlak at MA Muhammadiyah 01 Jember. The background of this study is based on teachers who still rely on conventional methods such as lectures in delivering material so that students tend to be less active in class, and this discussion method is designed to determine the extent to which students understand the material that has been delivered. The study used a qualitative approach with a case study type, through observation, interview and documentation techniques. The discussion method has proven effective in enhancing students' ability to express opinions, think critically, and collaborate. Supporting factors include a conducive classroom atmosphere and the teacher's role as a facilitator, while time constraints are the main obstacle.